A Systematic Review and Narrative Synthesis of Interventions to Address Substance Use Disorders and Other Mental Health Disorders in Prison Settings With a Focus on Low- and Middle-Income Countries - Jordan, Ashly E. (Criminal justice and behavior, 2023)
Interventions to treat substance use disorders (SUDs) and other mental health disorders (MHDs) in prison settings vary in both availability and effectiveness across contexts. Furthermore, incomplete characterization of intervention efficacy and/or effectiveness impacts the ability to know whether an intervention with demonstrated effectiveness in one setting will be effective in another setting. We systematically reviewed the literature for studies of interventions for SUDs and other MHDs conducted in prison settings, and synthesized the identified interventions and identified evidence gaps. Search strategies yielded 9,599 articles published between January 1, 2010, and December 31, 2020. A total of 82 articles were identified as eligible with interventions presented for SUDs (n = 52), for MHDs (n = 23), and for SUDs/MHDs (n = 7). Findings point to a narrow range of interventions of demonstrated effectiveness and to important gaps in the evidence-base for which high-quality research, particularly in low- and middle-income settings, is needed.